Investigating the relationship between bedtime procrastination, sleep quality and life satisfaction - Lee, Lin Qin (Nanyang Technological University, 2024)
A convergent mixed-method approach was used to explore the relationship between sleep quality, bedtime procrastination (BtP), and life satisfaction. 108 undergraduates were recruited in Singapore, of whom 100 were involved in the quantitative study and 8 in the qualitative study. The quantitative study mainly employed t test and hierarchical regression analyses while the qualitative study utilized thematic analysis. The quantitative study revealed that BtP and sociodemographic factors such as age, gender, and academic year of study were not associated with low life satisfaction. However, poor sleep quality was significantly associated with low life satisfaction. Although most undergraduates’ sleep efficiency was more than 85%, this was not consistent with their irregular sleep timings as they would wake up later despite their late bedtimes. The qualitative study revealed that one of the salient reasons for indulging in BtP from the eight themes and 12 subthemes was to feel relaxed from their academic demands and to increase their life satisfaction. A joint display table of consolidated data showed no link between BtP and low life satisfaction. However, as academic stress is inevitable, this study also emphasised healthier approaches to mitigate BtP and poor sleep quality.